Expansile crosslinked polymersomes for pH sensitive delivery of doxorubicin. (7th October 2015) - Liu, Xifeng; Yaszemski, Michael J.; Lu, Lichun
Abstract : Shell crosslinked polymersomes self-assembled by amphiphilic chains showed pH-responsive swelling through acidic cleavage of the hydrophobic content. Abstract : We report a new crosslinked polymersome with pH-responsive swelling properties through acidic hydrolysis of hydrophobic contents from the amphiphilic polymer chains. Its unique stability under physiological conditions and large swelling capability under low pH conditions give this polymersome promising potential for anticancer drug delivery.